2008
DOI: 10.1007/s11270-007-9597-4
|View full text |Cite
|
Sign up to set email alerts
|

Stable Incorporation of Co2+ into Ferrite Structure at Ambient Temperature: Effect of Operational Parameters

Abstract: Removal of heavy metals (HM) from industrial wastewater is of primary environmental importance. The seeded ambient temperature ferrite process, in which heavy metals are removed from solution by their incorporation into a magnetite structure, is an attractive alternative for both complete metals separation and generation of stable magnetic sludge. Despite its potential, the effects of various operational parameters on the composition and stability of the final product are not fully understood to-date. The curr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…In recent years, numerous studies on the treatment of wastewater and technological solutions by ferritization were carried out. The process of extraction of cobalt ions from concentrated solutions was explored in paper [4]. Inclusion of Со +2 ions into the ferrite structure and chemical stability of sediments was indicated.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
See 2 more Smart Citations
“…In recent years, numerous studies on the treatment of wastewater and technological solutions by ferritization were carried out. The process of extraction of cobalt ions from concentrated solutions was explored in paper [4]. Inclusion of Со +2 ions into the ferrite structure and chemical stability of sediments was indicated.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…Given a decrease in the oil stocks in the world, mankind has begun to look for alternative sources in order to obtain fuel whose production volumes grow every year. Conversion of synthesis-gas to liquid hydrocarbons using the Fischer-Tropsch process (FT-synthesis) [1][2][3][4] is an alternative technique for obtaining the motor fuel.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, numerous studies have been conducted on wastewater treatment by ferritization (Chaiyaraksa & Klaikeow 2006;Pritosiwi 2012). The authors (Morgan et al 2001;Petrick et al 2008) demonstrated incorporation of HM ions into ferrite structure. In papers (Kochetov et al 2010;Heuss-Aßbichler et al 2016) the ferritisation process was used for treatment of rinsing and concentrated coppercontaining water, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…The the bigger the grain size and magnetization level, the higher the removal efficiency of the magnetic filter. The characteristics of the final product will depend on the formation conditions (Petrick et al, 2008). By controlling these parameters it is possible to obtain an increase on grain size and magnetization levels (Ayyappan et al, 2009).…”
Section: Introductionmentioning
confidence: 99%